Pendidikan dan Pembalajaran di SD/MI - Suparlan ` Suparlan (FONDATIA, 2017)
Education is a demand to an immature human being to prepare to fulfill his or her own life's duties or briefly: education is a demand for human growth from birth to adulthood. In a physical and spiritual sense. Learning is a process whereby a behavior arises or changes because of a response to a situation. Basic education is the beginning of the world pendididkan. In it children are introduced to various basic foundations of knowledge, ranging from reading, arithmetic, singing that is not daptkan in secondary school sperti junior / high school. For that in basic education is very pital for the growth and development of sianak pengegtahuan, because to be able to proceed to further education it must master all the basics of the science.